Efficacy of Ocimum Sanctum against Alternaria Causing Diseases on Medicinal Plants - Ojha, Shruti; Goyal, Mamta; Chittoriya, Deepika (International Journal of Scientific Research in Biological Sciences, 2021)
Ocimum sanctum extracts prepared in methanol were tested for their antifungal activity against Alternaria alternata isolated from two important medicinal plants including Aegle marmelos and Emblica officinalis. Leaf, shoot, and flowers of O. sanctum were screened individually for the antifungal activity. Disc diffusion method was conducted against Alternaria species for analyzing the antifungal properties of the medicinal plant. Zone of inhibition was measured for evaluating the antifungal activity of the methanolic extracts tested against the test fungal strain. Commercial fungicide at a similar protocol was taken as control. Although all the tested plant parts showed positive results of phytopathogenic growth inhibition, but the leaf extracts showed comparatively better effect than the flower and stem extracts. For both the diseased plants including A. marmelos and E. officinalis, leaf and flower extracts showed comparatively better results than stem. The consequences of using plant parts of O. sanctum as botanical fungicides against the fungal pathogen Alternaria have been discussed. The botanical fungicides could be a potential alternative to the commercial fungicides which cause damage to crop and plant development.